2018
DOI: 10.1523/jneurosci.3619-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Is Transiently Reactivated in Injured Nerves to Promote c-Jun Elevation and Schwann Cell Dedifferentiation

Abstract: Schwann cells (SCs) are endowed with a remarkable plasticity. When peripheral nerves are injured, SCs dedifferentiate and acquire new functions to coordinate nerve repair as so-called repair SCs. Subsequently, SCs redifferentiate to remyelinate regenerated axons. Given the similarities between SC dedifferentiation/redifferentiation in injured nerves and in demyelinating neuropathies, elucidating the signals involved in SC plasticity after nerve injury has potentially wider implications. c-Jun has emerged as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 81 publications
(135 reference statements)
4
55
1
Order By: Relevance
“…Many pivotal studies over the past 10 years have eloquently and thoroughly demonstrated the role of the PI3K/AKT/mTOR pathway on SC myelination in vivo (Beirowski et al, 2017;Cotter et al, 2010;Figlia et al, 2017;Goebbels et al, 2012;Norrmén et al, 2014Norrmén et al, , 2018Sherman et al, 2012 Gregorio et al, 2018;Liu et al, 2017;O'Brien et al, 2014;Sullivan et al, 2007). Consistent with diabetic models, we did not observe reduced CMAP amplitude or motor strength/coordination in INSR/IGF1R SCKO mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Many pivotal studies over the past 10 years have eloquently and thoroughly demonstrated the role of the PI3K/AKT/mTOR pathway on SC myelination in vivo (Beirowski et al, 2017;Cotter et al, 2010;Figlia et al, 2017;Goebbels et al, 2012;Norrmén et al, 2014Norrmén et al, , 2018Sherman et al, 2012 Gregorio et al, 2018;Liu et al, 2017;O'Brien et al, 2014;Sullivan et al, 2007). Consistent with diabetic models, we did not observe reduced CMAP amplitude or motor strength/coordination in INSR/IGF1R SCKO mice.…”
Section: Discussionsupporting
confidence: 82%
“…The PI3K/AKT/mTOR activity is observed early after PNS injury and has been shown to be important for SC dedifferentiation (Norrmén et al, ), so we asked whether INSR/IGFR1 signaling might contribute to these effects. To assess dedifferentiation and debris clearance, we transected the sciatic nerves of WT and SCKO mice and sacrificed the animals 5 days afterward.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous analysis of uninjured nerves had revealed an increase in p-AKT in the cKO (Ma et al 2015), and at 1 d after injury, there was a similar increase in AKT phosphorylation at Thr308 and Ser473, which are catalyzed by PDK1 and mTORC2, respectively (Andjelković et al 1997; Sarbassov et al 2005) (Figure 2). At 1 d after injury, there is little change in p-AKT in wild type mice (Norrmén et al 2018; Ronchi et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a number of intracellular pathways that potentially regulate c‐Jun levels have been identified. This includes the Rac1–MKK7–JNK pathway and mTORC, which elevate c‐Jun and have been implicated as upstream activators of c‐Jun after nerve injury, and the cAMP pathway that suppresses c‐Jun (Arthur‐Farraj et al, ; Monje, Soto, Bacallao, & Wood, ; Norrmén et al, ; Shin et al, ). Histone deacetylase 2 (HDAC2), which is activated in injured nerves, also downregulates c‐Jun (Brügger et al, ; reviewed in Jacob, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%